Over-reliance on land for carbon dioxide removal in net-zero climate pledges - Kate Dooley; Kirstine Lund Christiansen; Jens Friis Lund; Wim Carton; Alister Self (Nature Communications)
Abstract Achieving net-zero climate targets requires some level of carbon dioxide removal. Current assessments focus on tonnes of CO2 removed, without specifying what form these removals will take. Here, we show that countries’ climate pledges require approximately 1 (0.9–1.1) billion ha of land for removals. For over 40% of this area, the pledges envisage the conversion of existing land uses to forests, while the remaining area restores existing ecosystems and land uses. We analyse how this demand for land is distributed geographically and over time. The results are concerning, both in terms of the aggregate area of land, but also the rate and extent of land use change. Our findings demonstrate a gap between governments’ expected reliance on land and the role that land can realistically play in climate mitigation. This adds another layer to the observed shortcomings of national climate pledges and indicates a need for more transparency around the role of land in national climate mitigation plans.